Correlation and path coefficient studies in garlic (Allium sativum L.) - S R Bhonde, R P Gupta, R K Singh, B K Dubey (Journal of Spices and Aromatic Crops, 2011)
Correlation and path coefficient analysis were studied in 32 promising germplasm lines of garlic (Allium sativum) at Karnal (Haryana). Marketable yield was positively and significantly correlated with leaves plant-1, bulb diameter, bulb size index, weight of 20 bulbs and cloves bulb-1 at genotypic and phenotypic levels and negatively correlated with weight of 50 cloves at both levels. Gross yield was positively and significantly correlated with plant height, neck thickness and negatively correlated with clove diameter and clove size index at genotypic and phenotypic levels, indicating that selection based on these traits will help in increasing the yield. At genotypic level, traits such as leaves plant-1, clove diameter, cloves bulb-1 and weight of 50 cloves showed a positive direct effect on yield. Clove diameter had maximum positive direct effect (0.744) followed by weight of 50 cloves (0.547), cloves bulb-1 (0.313) and leaves plant-1 (0.288). The highest negative direct effect was noted for clove size index (-0.874), followed by neck thickness (-0.341), weight of 20 bulbs (-0.264) and plant height (-0.057). The estimates of direct and indirect effect on yield were more pronounced in genotypic path than phenotypic path coefficient. The study thus indicated that weight of 20 bulbs, bulb size index, weight of 50 cloves and cloves bulb-1 produced higher positive direct effect on yield and should be given emphasis during selection for improvement of garlic.